2018
DOI: 10.1038/s41598-018-26149-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chromatin states and gene expression during HSN neuronal maturation is mediated by EOR-1/PLZF, MAU-2/cohesin loader, and SWI/SNF complex

Abstract: Newborn neurons mature by distinct and sequential steps through the timely induction of specific gene expression programs in concert with epigenetic changes. However, it has been difficult to investigate the relationship between gene expression and epigenetic changes at a single-cell resolution during neuronal maturation. In this study, we investigated the maturation of hermaphrodite-specific neurons (HSNs) in C. elegans, which provided the link between chromatin dynamics, gene expression, and the degree of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…At the genes that gain both accessibility and expression (Group B), an analysis of TF motifs indicated that chromatin decompaction may well be a secondary effect of TF binding, as the TFs recruit additional complexes that in turn regulate chromatin opening. Notably, the bZIP TFs that co-map with Group B loci as well as Onecut1/2, the CEH-48 homologue, recruit the CBP/p300 histone acetyltransferase, and EOR-1 cooperates with the SWI/SNF chromatin remodeler 51 , 54 – 57 . Thus, depending on the chromatin factors that are recruited, different TFs may trigger different degrees of chromatin opening (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the genes that gain both accessibility and expression (Group B), an analysis of TF motifs indicated that chromatin decompaction may well be a secondary effect of TF binding, as the TFs recruit additional complexes that in turn regulate chromatin opening. Notably, the bZIP TFs that co-map with Group B loci as well as Onecut1/2, the CEH-48 homologue, recruit the CBP/p300 histone acetyltransferase, and EOR-1 cooperates with the SWI/SNF chromatin remodeler 51 , 54 – 57 . Thus, depending on the chromatin factors that are recruited, different TFs may trigger different degrees of chromatin opening (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the non-derepressed Group C, which nonetheless gained ATAC-seq sensitivity, the only motifs significantly enriched were for EOR-1, DAF-12/NHR-48 and ZTF-3. Importantly, all three of these factors have been shown to bind enhancers during C. elegans development 47 , 51 .…”
Section: H3k9me Restricts Enhancer Activationmentioning
confidence: 99%